DIGITAL ENGAGEMENT STRATEGIES AND THEIR IMPACT ON EFL TEACHER ACHIEVEMENT IN DISTANCE EDUCATION - Benny Nugraha; Marwito Wihadi; Le Thi Minh Thao (English Review: Journal of English Education, 2025)
Distance education necessitates a nuanced understanding of student diversity to optimize academic outcomes. This study, conducted at Universitas Terbuka, aimed to identify key learner characteristics influencing academic success in an online English Language Education Program. It specifically investigated the demographic profile, digital readiness, independent learning readiness, English proficiency, and learning styles of in-service teacher students, focusing on their academic performance in the Teaching English as a Foreign Language (TEFL 1) course from 2017.2 to 2024.2. Employing an explanatory sequential mixed-methods approach with quantitative descriptive statistics and qualitative in-depth interviews, data were collected from a purposive sample of 20 in-service teacher students. This research addresses a critical gap by comparing how high-achieving (HA) and low-achieving (LA) students engage with digital learning environments and utilize distinct learning strategies. Key findings indicate that HA students effectively leverage structured digital resources like modules, English podcasts, and AI applications, complemented by consistent daily study. In contrast, LA students, despite higher social media activity for "learning," often depend on peer discussions for tutorial tasks, reflecting less independent problem-solving. This comparative analysis underscores that effective digital learning is determined by the quality and nature of engagement, not mere access or duration, offering insights for designing targeted interventions to enhance academic success in distance EFL teacher education.